Decreased expression and activity of neprilysin in Alzheimer disease are associated with cerebral amyloid angiopathy. - Miners, J; Van Helmond, Z; Chalmers, K; Wilcock, G; Love, S; Kehoe, P (2006)
Neprilysin (NEP) degrades amyloid-beta (Abeta) and is thought to contribute to its clearance from the brain. In Alzheimer disease (AD), downregulation of NEP has been suggested to contribute to the development of cerebral amyloid angiopathy (CAA). We examined the relationship among NEP, CAA, and APOE status in AD and elderly control cases. NEP was most abundant in the tunica media of cerebrocortical blood vessels and in pyramidal neurons. In homogenates of the frontal cortex, NEP protein levels were reduced in AD but not significantly; NEP enzymatic activity was significantly reduced in AD. Immunohistochemistry revealed a reduction of both vascular and parenchymal NEP. The loss of vessel-associated NEP in AD was inversely related to the severity of CAA, and analysis of cases with severe CAA showed that levels of vascular NEP were reduced to the same extent in Abeta-free and Abeta-laden vessels, strongly suggesting that the reduction in NEP is not simply secondary to CAA. Possession of APOE epsilon4 was associated with significantly lower levels of both parenchymal and vascular NEP. Colinearity of epsilon4 with the presence of moderate to severe CAA precluded assessment of the independence of this association from NEP levels. However, logistic regression analysis showed low NEP levels to be a significant independent predictor of moderate to severe CAA.